MILITER DAN POLITIK IRAN PASCA REVOLUSI - , MOHAMMAD NUR S S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
More than two third of countries in Latin America, Asia, Africa and the Middle East has experienced various degree of military intervention in politics or pretorianism since 1945. Many resulted in recurring military takeover of the government or coup de etat and Iran was no exception. However, the situation has changed since the fall of Pahlavi Dynasty in Iran trough the Islamic Revolution of 1979. Although post revolutionary Iran encounters numerous military involvements in politics to some extent, none have been critical enough to result a military takeover of government. This transformation is a result of the ever evolving of the Iranian political institution since the introduction of Shiite Islam as a state religion more than three centuries ago up until now. Throughout its history, from time to time, the strength and effectiveness of Iranian political institution is improving and the establishment of an Iranian Constitution is one of the examples. Furthermore, the dynamics of the international system also plays a role in forming the military and political relation in Iran. Therefore, as long as the military abide by its constitution and foreign threat is still eminent, Iran shall not encounter those recurring events that overshadows the pre revolution period.